Interdisciplinary integration of nursing and psychiatry (INaP) improves dizziness‐related disability. (26th November 2019) - Gerretsen, Philip; Shah, Parita; Logotheti, Anastasia; Attia, Mohamed; Balakumar, Thushanthi; Sulway, Shaleen; Ranalli, Paul; Dillon, Wanda A.; Pothier, David D.; Rutka, John A.
Abstract : Objectives/Hypothesis: The traditional medical care model of "assess and refer" in a sequential fashion fails to recognize the complexities that arise due to overlapping physical and psychiatric comorbidities experienced by patients with chronic dizziness or imbalance, thus resulting in inadequate treatment outcomes. We aimed to evaluate the impact of a novel interdisciplinary approach to care that integrates nursing and psychiatry (INaP) on dizziness‐related disability. Study Design: Retrospective cohort study. Methods: We compared the change in clinical assessment scores (i.e., Dizziness Handicap Inventory [DHI], Dizziness Catastrophizing Scale) at approximately 8 months follow‐up between those who did (INaP+) and did not receive INaP (INaP−). Data from 229 patients with dizziness or imbalance referred to an interdisciplinary neurotology clinic in Toronto, Ontario, Canada were acquired from August 2012 to December 2016 and January 2011 to December 2013 for the INaP+ and INaP− groups, respectively. Results: A mean group difference in the percentage change in DHI scores was found, with greater reductions in dizziness‐related disability in the INaP+ group (n = 121) versus the INaP− group (n = 108). This remained significant after controlling for age, gender, baseline illness severity, and duration between baseline and follow‐up visits. Conclusions: The novel interdisciplinary approach of incorporating INaP appears to be more effective than interdisciplinary care without INaP in reducing dizziness‐related disability in patients with chronic dizziness or imbalance. Clinical settings should consider the addition of INaP to achieve better patient outcomes. Future studies are required to test the hypothesis that INaP is more efficient and cost‐effective than the traditional model of care. Level of Evidence: 3 Laryngoscope, 130:1800–1804, 2020